2020
DOI: 10.7554/elife.63430
|View full text |Cite
|
Sign up to set email alerts
|

Post-acute COVID-19 associated with evidence of bystander T-cell activation and a recurring antibiotic-resistant bacterial pneumonia

Abstract: Here, we describe the case of a COVID-19 patient who developed recurring ventilator-associated pneumonia caused by Pseudomonas aeruginosa that acquired increasing levels of antimicrobial resistance (AMR) in response to treatment. Metagenomic analysis revealed the AMR genotype, while immunological analysis revealed massive and escalating levels of T-cell activation. These were both SARS-CoV-2 and P. aeruginosa specific, and bystander activated, which may have contributed to this patient’s persistent symptoms an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 35 publications
2
19
0
Order By: Relevance
“…It is possible that the underlying prolonged inflammation that we have shown in long COVIDs causes activation and differentiation of T and B cells, and when this inflammation is constant, exhaustion and dysfunction of these cells will eventuate. Bystander activation of these un-activated naїve subsets into more activated phenotypes is evident in long COVID, and is consistent with observations in some acute severe patients 60,61 . Increased myeloid activation is associated with activation of the antigen processing and presentation machinery and up regulation of co-stimulatory molecules necessary for differentiation and polarisation of T and B cells.…”
Section: Discussionsupporting
confidence: 89%
“…It is possible that the underlying prolonged inflammation that we have shown in long COVIDs causes activation and differentiation of T and B cells, and when this inflammation is constant, exhaustion and dysfunction of these cells will eventuate. Bystander activation of these un-activated naїve subsets into more activated phenotypes is evident in long COVID, and is consistent with observations in some acute severe patients 60,61 . Increased myeloid activation is associated with activation of the antigen processing and presentation machinery and up regulation of co-stimulatory molecules necessary for differentiation and polarisation of T and B cells.…”
Section: Discussionsupporting
confidence: 89%
“…Dani et al, described long COVID symptoms, such as tachycardia, palpitation, orthostatic intolerance, breathlessness, and chest pain as the consequences of autonomic nervous system instability caused by deconditioning, hypovolemia or immune- or virus-mediated autonomic nervous system destruction [ 110 ]. In a case report of a COVID-19 patient with anti-microbial resistant Pseudomonas Aeruginosa infection, it was documented that 6 weeks after clearing of the viral infection, a significant number of activated T-cells and T-cells-specific for unrelated antigens were present, suggesting "a significant amount of by stander activation" which might contribute to recurring anti-bacterial-resistant infections [ 148 ]. A study measuring 96 immune response-associated proteins showed that even 40 days post-COVID-19 viral infection high levels of biomarkers related to innate anti-inflammatory and stress response were present [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, many of the published studies are based on small cohorts (several hundred COVID-19 patients were analyzed) and relied on self-reported outcomes which can embody potential biases due to, for example, exaggeration of symptoms. 14 There have also been a number of less commonly reported symptoms including ocular inflammation 15 , cardiac involvement 16,17 , autonomic instability 18 , recurrent pseudomonas infections 19 , persistent mucous secretion 20 , micro-structural changes to the brain 21 and Guillain-Barre syndrome. 22 .…”
Section: Introductionmentioning
confidence: 99%